2020
DOI: 10.1086/706820
|View full text |Cite
|
Sign up to set email alerts
|

Prison as a Criminal School: Peer Effects and Criminal Learning behind Bars

Abstract: We investigate peer effects on crime-specific recidivism using register data for the entire Danish prison population. We find that inmates do not acquire new criminal capital in prison (no introductory peer effects). For certain types of crimes, we find that inmates strengthen their criminal capital in prison because of exposure to offenders in their field of specialization (reinforcing peer effects). Our results accord with a theory of crime-specific knowledge transmission and network building: we find reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 65 publications
0
12
0
1
Order By: Relevance
“…[18][19][20] On the contrary, in prisons, staying with many criminal peers in a limited facility makes minor criminals frequently contact with hard-core and skilled criminals and possibly deepens their illegal involvement. [21][22][23] The peer effect on crime recidivism is strongly supported by recent empirical research in many countries. [24][25][26] We are especially interested in the influence of overcrowded prison facilities on criminal transition.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[18][19][20] On the contrary, in prisons, staying with many criminal peers in a limited facility makes minor criminals frequently contact with hard-core and skilled criminals and possibly deepens their illegal involvement. [21][22][23] The peer effect on crime recidivism is strongly supported by recent empirical research in many countries. [24][25][26] We are especially interested in the influence of overcrowded prison facilities on criminal transition.…”
Section: Introductionmentioning
confidence: 92%
“…This paper focuses on criminal transitions occurring inside and outside of prison, which respectively have been conceptualized in popular terms “broken windows effect” and “prison as a crime school”; the broken windows theory states that accumulation of low level offenses in a community, if not adequately controlled, acts as a social pressure that leads to more serious crimes 18‐20 . On the contrary, in prisons, staying with many criminal peers in a limited facility makes minor criminals frequently contact with hard‐core and skilled criminals and possibly deepens their illegal involvement 21‐23 . The peer effect on crime recidivism is strongly supported by recent empirical research in many countries 24‐26 …”
Section: Introductionmentioning
confidence: 99%
“…Studies linking the prison experience to criminal trajectories could also serve as inspiration for future work on gang networks. These studies treat the prison experience as a potential turning point in the criminal trajectories of offenders, either to examine against outcome measures like recidivism (Damm and Gorinas, 2020; Roxell, 2011), or even to investigate whether prison has had an impact on the social networks themselves (Volker et al , 2016). Although none of these studies focused on gang members specifically, incarceration periods may also act as important turning points in the career of gang members, who may or may not be interested in reintegrating their pre-incarceration gang network, after release.…”
Section: Gang Network In Prisonmentioning
confidence: 99%
“…While each of these hypotheses certainly has theoretical merit, their empirical grounding is in short supply. The schools of crime (Bayer et al, 2009;Harris et al, 2018;Damm & Gorinas, 2016;Ouss, 2011) and strain (Listwan et al, 2013;Morris et al, 2012;Zweig et al, 2015) hypotheses have each been tested only a handful of times. And while some studies have shown that being labeled as a felon or criminal justice processing in general leads to increased reoffending (e.g., Chiricos, Barrick, Bales, & Bontrager, 2007;Gatti, Tremblay, & Vitaro, 2009), the prediction of labeling theory that the stigma of an arrest or incarceration record leads to identity change and increased reoffending has never been adequately tested.…”
Section: Implications For Policy and Future Researchmentioning
confidence: 99%
“…It is therefore incumbent upon criminologists and policymakers to understand precisely how incarceration can be made less criminogenic than it currently is. If it turns out, for example, that homophily in cell assignments has a substantive influence on the likelihood and type of reoffending (e.g., Damm & Gorinas, 2016;Ouss, 2011), knowledge on the logistics and impacts of inmates' assignments to specific types of prisons, units, and cells themselves would need to be expanded significantly.…”
Section: Implications For Policy and Future Researchmentioning
confidence: 99%